Influence of monsoon system on α‐HCH fate in Asia: A model study from 1948 to 2008. Issue 12 (21st June 2013) - Xu, Yue; Tian, Chongguo; Zhang, Gan; Ming, Lili; Wang, Yan; Chen, Yingjun; Tang, Jianhui; Li, Jun; Luo, Chunling
Abstract: [1] The Chinese Gridded Pesticide Emission and Residue Model was applied to simulate long‐term environmental fate of α‐hexachlorocyclohexane (HCH) in Asia spanning 1948 to 2008. The simulation identifies the southern Tibetan Plateau and the margin of the Asian monsoon regime from the northeast area of the Tibetan Plateau to the Northeast China as sink areas. This spatial pattern of sink distribution is closely related to the summer monsoon activities in Asia. Wet deposition associated with the summer monsoon (June to August) is responsible for at least half of the α‐HCH mass entering into the sink areas. After deposition, relatively low temperature and high soil organic matter in the sink areas are favorable for α‐HCH detention. Chinese and Indian sources are the major contributors to α‐HCH contamination over the monsoon margin and the Tibetan Plateau, driven by the East Asian summer monsoon and South Asian summer monsoon, respectively. Key Points: α‐HCH distributed along monsoon margin in Asia Wet deposition is the major input ways low temperature and high soil organic matter are favourable for HCH detention